Impact of COVID-19 on the histopathological aspect of the placenta during pregnancy - Anak Agung Ngurah Jaya Kusuma (Majalah Obstetri & Ginekologi, 2023)
The coronavirus disease 2019 (COVID-19) is still classified as a world pandemic. This disease can affect numerous systems of the human body. Pregnant women are classified as a vulnerable group since COVID-19 can cause high morbidity and mortality. Angiotensin-converting enzyme-2 (ACE-2) acts as a COVID-19 receptor, and this receptor is also present in the placenta. The placenta plays a significant part in the fetus, especially protecting it from harmful conditions. Since only a few studies are available, COVID-19’s influence on the placenta in pregnancy needs to be discussed further. The SARS-CoV-2-infected pregnant woman’s placenta showed histopathological alterations. Viral particles were detected on syncytiotrophoblast and chorionic villi vascular endothelial cells. Some studies show inflammatory conditions are not prominent in SARS-CoV-2 positive infection. This, perhaps due to the placenta’s immunological reaction, plays a significant role. The SARS-CoV-2 disorder tends to cause abnormalities within the placental tissue. Fetal vascular malperfusion (FVM) and maternal vascular malperfusion (MVM) are the most frequent findings from the studies included.